PREGNANCY: AN OVERVIEW OF C-SECTION DELIVERY - Kumar, Atul; Khinchi, M.P.; Khan, Mohd. Shahid; Singh, Surya Pratap; Nagar, Lokesh (Asian Journal of Pharmaceutical Research and Development, 2017)
Cesarean section (CS) is a surgical procedure used to deliver one or more babies. CS is usually performed when vaginal delivery will put the mother or child’s health or life at risk. Since CS also involves risk for adverse outcome for both mother and child, concern has been expressed regarding its increased use. The purpose of this paper to know about Some women may require an urgent and unplanned caesarean even though they were expected to have a normal vaginal birth. A cesarean section is the delivery of a baby through a cut (incision) in the mother's belly and uterus. It is often called a C-section. In most cases, a woman can be awake during the birth and be with her newborn soon afterward.